Charlie the caterpillar - DeLuise, Dom.; Santoro, Christopher (New York : Simon and Schuster Books for Young Readers, 1990)
A caterpillar is rejected by various groups of animals, until he achieves his beautiful wings and is able to befriend a similarly unhappy caterpillar.
4.5
K-3
K-3
School Library Journal
280
Keywords: Caterpillars -- Fiction; Butterflies -- Fiction; Animals -- Fiction; Friendship -- Fiction; Caterpillars -- Fiction; Butterflies -- Fiction; Animals -- Fiction; Friendship -- Fiction